2019
DOI: 10.3390/su11113066
|View full text |Cite
|
Sign up to set email alerts
|

What Attitudes Toward Refugees Do Future European Teachers Have? A Comparative Analysis between France and Spain

Abstract: (1) Background. The increase in international conflicts and humanitarian crises has led to an increase in the movement of people to Europe. The legal and moral commitments of the European Union require the incorporation and integration of such refugees. In this sense, the school and its teaching staff are a key agent in the challenge of integrating newly arrived students. This research analyses attitudes towards inclusive European citizenship, the recognition of rights, and feelings of threat and affective rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…This is in line with the results of more general surveys, which suggested that attitudes and perceptions towards people from refugee and migrant backgrounds are influenced by the personal characteristics of the respondents, such as gender and educational level (Bešić et al, 2020;Soriano and Cala, 2019). More specifically, there are indications that women and people with higher educational levels tend to have a more positive attitude towards people from migrant and refugee backgrounds (Bešić et al, 2020;Soriano and Cala, 2019). Personal experiences of migration are also believed to be an important factor (Becker, 2019).…”
Section: State Of Researchsupporting
confidence: 82%
See 2 more Smart Citations
“…This is in line with the results of more general surveys, which suggested that attitudes and perceptions towards people from refugee and migrant backgrounds are influenced by the personal characteristics of the respondents, such as gender and educational level (Bešić et al, 2020;Soriano and Cala, 2019). More specifically, there are indications that women and people with higher educational levels tend to have a more positive attitude towards people from migrant and refugee backgrounds (Bešić et al, 2020;Soriano and Cala, 2019). Personal experiences of migration are also believed to be an important factor (Becker, 2019).…”
Section: State Of Researchsupporting
confidence: 82%
“…Moreover, a survey conducted in the USA found that female PE teachers had a more positive attitude and felt more comfortable about dealing with students from diverse backgrounds than their male colleagues (Columna et al, 2010). This is in line with the results of more general surveys, which suggested that attitudes and perceptions towards people from refugee and migrant backgrounds are influenced by the personal characteristics of the respondents, such as gender and educational level (Bešić et al, 2020;Soriano and Cala, 2019). More specifically, there are indications that women and people with higher educational levels tend to have a more positive attitude towards people from migrant and refugee backgrounds (Bešić et al, 2020;Soriano and Cala, 2019).…”
Section: State Of Researchsupporting
confidence: 64%
See 1 more Smart Citation
“…It should be mentioned that in order to obtain these results, three items of the scale had to be replaced, considering what also happened in previous research where some items were problematic and had to be removed [ 47 , 48 ]. It is probable that these items had to be replaced with others that were more culturally adjusted to represent the attitudes towards Maghrebis in Spain, and to fit better with the data [ 49 ]. Likewise, according to the scale’s validity, the factor structure of the AMES was satisfactorily examined using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA).…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be due to geopolitical forces. That is, having in mind the French political scene and its refugee discourse with its restricting parameters, and the more linear integration framework in Spain (Soriano & Cala, 2019), the geopolitical discourse and the dynamics of the host country also governs the perception of the monument, be it international media outlets or local ones.…”
Section: Struggling With the Voidmentioning
confidence: 99%